1999
DOI: 10.1093/brain/122.7.1383
|View full text |Cite
|
Sign up to set email alerts
|

Spinal root and plexus hypertrophy in chronic inflammatory demyelinating polyneuropathy

Abstract: MRI was performed on the spinal roots, brachial and lumbar plexuses of 14 patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Hypertrophy of cervical roots and brachial plexus was demonstrated in eight cases, six of whom also had hypertrophy of the lumbar plexus. Of 11 patients who received gadolinium, five of six cases with hypertrophy and one of five without hypertrophy demonstrated enhancement. All patients with hypertrophy had a relapsing-remitting course and a significantly longer dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
4
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(136 citation statements)
references
References 16 publications
8
122
4
2
Order By: Relevance
“…Enlarged spinal roots may be identified in patients being investigated for demyelinating neuropathy as in our first case. N e rve root enhancement with gadolinium, seen in our patient, is sometimes found in inflammatory demyelinating neuropathies 5,9,11 . When CIDP evolves slowly and its pro g re s s i o n is more insidious it may be difficult to distinguish it from a hypert rophic CMT.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Enlarged spinal roots may be identified in patients being investigated for demyelinating neuropathy as in our first case. N e rve root enhancement with gadolinium, seen in our patient, is sometimes found in inflammatory demyelinating neuropathies 5,9,11 . When CIDP evolves slowly and its pro g re s s i o n is more insidious it may be difficult to distinguish it from a hypert rophic CMT.…”
Section: Discussionsupporting
confidence: 57%
“…Thickened peripheral nerves were seen in 11% in one larg e s e r i e s 3 . Although exceedingly rare, there have been re c o rded cases of CIDP presenting with spinal cord compression due hypertrophic spinal roots [5][6][7][8][9][10][11][12][13] . We re p o rt two patients with CIDP of long evolution with cervical spinal compression due to hypertrophic roots.…”
Section: P O L I Rr a D I C U L O N E U Ropatia Desmielinizante Inflamentioning
confidence: 99%
“…MRI may reveal cranial nerve hypertrophy and enhancement even without clinical deficit [1]. MR evidence of spinal root hypertrophy occurs in 60% of adult patients, typically those with long disease duration [2]. Root thickening may be seen in paediatric CIDP but, unlike that in our patient, is generally mild.…”
mentioning
confidence: 58%
“…1 A magnetic resonance imaging (MRI) study of 14 cases of CIDP found cervical and brachial plexus hypertrophy in 8. 4 These cases had significantly longer disease courses (mean 15.9 years) than those cases without hypertrophy (mean 3.3 years, p = 0.05). The phenomenon is most likely due to the chronic effects of the disease; however, two of the cases with hypertrophy had short disease courses (7 and 18 months), but both patients were moderately to severely disabled, suggesting that nerve hypertrophy may be a marker of disease activity.…”
Section: Introductionmentioning
confidence: 80%